smFISH_batchRun: A smFISH image processing tool for single-molecule RNA Detection and 3D reconstruction - John, Nimmy S.; Lee, ChangHwan (Software impacts, 2025)
Single-molecule RNA imaging has been made possible with the recent advances in microscopy methods. However, systematic analysis of these images has been challenging due to the highly variable background noise, even after applying sophisticated computational clearing methods. Here, we describe our custom MATLAB scripts that allow us to detect both nuclear nascent transcripts at the active transcription sites (ATS) and mature cytoplasmic mRNAs with single-molecule precision and reconstruct the tissue in 3D for further analysis. Our codes were initially optimized for the C. elegans germline but were designed to be broadly applicable to other species and tissue types. •smFISH_batchRun allows precise detection of RNA at the single molecule level for widefield microcopy images.•The scripts highlighted here can allow users to detect and visualize the detection and confirm that it is indeed accurate or adjust the thresholds as needed.•Our scripts collect the 3D spatial coordinates of Active Transcription Sites (ATS), cytoplasmic mRNA and their associated nuclei and could be adapted to other systems as well.